Pathogenetic identification in ticks and yaks from Zoige County, China - Xiang, Yang; He, Liang; Zhu, Liangquan; Xiao, Chendong; Pan, Yao; Chen, Tianxiang; Zheng, Wei; Yuan, Dongbo (Frontiers in Cellular and Infection Microbiology, 2024)
Background:Ticks represent a significant vector for the transmission of infectious diseases, with the prevalence of tick-borne diseases becoming a prominent global health concern in recent decades. Anaplasma spp., Rickettsia spp., and Piroplasma have been identified as significant pathogens with the potential to impact human and animal health. However, there is a dearth of data concerning the prevalence of these pathogens in the eastern Tibetan Plateau, China.MethodsIn this study, a total of 643 Dermacentor silvarum and 314 Haemaphysalis longicornis were identified through the application of morphological and molecular identification techniques on 957 ticks collected from yaks in Zoige County. The assessed of Anaplasma spp., Rickettsia spp., Theileria spp., and Babesia spp. was assessed in 957 ticks and 96 blood samples collected from yaks.ResultsSignificant discrepancies were observed in the positivity rates for the four pathogens among the tick species and sampling sites. The identification of different species within the four pathogens was based on the analysis of the 16S rRNA of Anaplasma spp., the ompA and ompB genes of Rickettsia spp., and the 18S rRNA of Theileria spp. and Babesia spp. The prevalence ranges of the four pathogens are 9.9-50.2%, 29.5-100%, 16.2-46.4%, and 14.5-58.4%, respectively.ConclusionIn view of the growing zoonotic risks, further investigations into the prevalence of additional pathogens in ticks and animals, including livestock, in the eastern Tibetan Plateau, China, are essential.